Design Approach for Sub-surface Flow Constructed Wetlands - Ghimire, Anish; KC, Ajay Kumar; Thapa, Bijay (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Constructed Wetlands are an engineered wastewater treatment system that tries to mimic the natural biological, physical and chemical processes to treat wastewater. It is emerging as a cost-effective decentralized wastewater treatment solution in the communities where there is availability of inexpensive lands and lack of skilled operators. Different design approaches have been followed and design parameters based on different literatures have been chosen to design a Sub-surface Flow Constructed Wetlands. A simplified design approach well suited to climatic needs to be developed to maintain the cost effectiveness of the system. The kinetic parameters involved in the treatment should be selected properly in order to get the effective design of the system. DOI: http://dx.doi.org/10.3126/hn.v10i0.7102 Hydro Nepal Vol.10 January 2012 42-47